Persepsi Mahasiswa IAIN Kerinci terhadap Pelaksanaan Perkuliahan Daring - Miftahul Jannah; Rhomiy Handican; Zakkya Zakkya (Institut Agama Islam Negeri Kerinci, Indonesia, 2020)
Abstract.Online lectures are government policies that are the main means of learning during the Covid-19 pandemic. This is also applied at the Institut Agama Islam Negeri (IAIN) Kerinci, which follows the government's recommendation to carry out online activities using online application facilities, such as whatsapp groups, zoom, google classroom, and other application media. This research aims to determine students perceptions of online lectures. During the pandemic related to the Covid-19 outbreak, students carried out activities online. Analysis of the data used to complete this research using a Likert scale survey method with a total sample of 51 respondents who are students of the State Islamic Institute (IAIN) Kerinci. The results of the study indicate that in the implementation of distance learning there are several dimensions that must be the main concern. These dimensions include: Material or teaching mode, student interaction, and learning atmosphere. Therefore, this study focuses on students' perceptions of the dimensions of the implementation of online lectures.